Dampak Rekrutmen Pantarlih terhadap Efektivitas Data dan Pengelolaan Anggaran Biaya pada Pilkada 2024 di Provinsi Lampung - Masthuroh Masthuroh; Hasbullah Hasbullah; Muhadi Muhadi; Dwi Nurahman (Business and Enterpreneurship Journal (BEJ), 2024)
This study aims to analyze the impact of the recruitment of the Voter Data Update Committee (Pantarlih) on the effectiveness of voter data management and budget costs in the 2024 Regional Head Election (Pilkada) in Lampung Province. Pantarlih plays an important role in ensuring accurate and up-to-date voter data, which is the basis for implementing the Pilkada. In addition, this study also examines the influence of the Pantarlih recruitment process on efficient and targeted budget management. The study was conducted using qualitative methods through in-depth interviews with stakeholders and analysis of related documents. The results of the study indicate that a selective and professional recruitment process has a positive impact on the effectiveness of voter data management and budget use, which in turn improves the quality of Pilkada implementation in Lampung Province. Keywords: Pantarlih, 2024 Pilkada, Lampung Province, Voter Data, Budget Managemen